Obestatin controls the ubiquitin–proteasome and autophagy–lysosome systems in glucocorticoid‐induced muscle cell atrophy. Issue 6 (3rd July 2017) - Cid‐Díaz, Tania; Santos‐Zas, Icía; González‐Sánchez, Jessica; Gurriarán‐Rodríguez, Uxía; Mosteiro, Carlos S.; Casabiell, Xesús; García‐Caballero, Tomás; Mouly, Vincent; Pazos, Yolanda; Camiña, Jesús P.
Abstract: Background: Many pathological states characterized by muscle atrophy are associated with an increase in circulating glucocorticoids and poor patient prognosis, making it an important target for treatment. The development of treatments for glucocorticoid‐induced and wasting disorder‐related skeletal muscle atrophy should be designed based on how the particular transcriptional program is orchestrated and how the balance of muscle protein synthesis and degradation is deregulated. Here, we investigated whether the obestatin/GPR39 system, an autocrine/paracrine signaling system acting on myogenesis and with anabolic effects on the skeletal muscle, could protect against glucocorticoid‐induced muscle cell atrophy. Methods: In the present study, we have utilized mouse C2C12 myotube cultures to examine whether the obestatin/GPR39 signaling pathways can affect the atrophy induced by the synthetic glucocorticoid dexamethasone. We have extended these findings to in vitro effects on human atrophy using human KM155C25 myotubes. Results: The activation of the obestatin/GPR39 system protects from glucocorticoid‐induced atrophy by regulation of Akt, PKD/PKCμ, CAMKII and AMPK signaling and its downstream targets in the control of protein synthesis, ubiquitin–proteasome system and autophagy–lysosome system in mouse cells. We compared mouse and human myotube cells in their response to glucocorticoid and identified differences in both the triggering of the atrophic program and the response to obestatin stimulation. Notably, we demonstrate that specific patterns of post‐translational modifications of FoxO4 and FoxO1 play a key role in directing FoxO activity in response to obestatin in human myotubes. Conclusions: Our findings emphasize the function of the obestatin/GPR39 system in coordinating a variety of pathways involved in the regulation of protein degradation during catabolic conditions.